The Development of Learning Video Media Based on Swishmax and Screencast O-Matic Software through Contextual Approach - Kholifah, Siti (Dinamika Pendidikan, 2016)
This research aims to develop a learning media video based on swishmax dan screencast o-matic software through contextual approach. The study used ADDIE development model which consisted of five stages, namely, analysis, design, development, implementation, and evaluation. Before using the learning video media, firstly it was tested by media experts and subject experts. Then; it needed students’ feedback by using questionnaires about the media. The results of the experts and students’ questionnaires show that the media is very good and feasible to be used. The effectiveness of the media was analyzed by t-test. The mean score of experimental class is 85.03; whereas the mean score of control class is only 79.00. By using t test scores, its score is 3.30 and more than 1.997; then Ho is rejected. Therefore; it can be concluded that learning by using the learning video media based swishmax and screencast o-matic software through the contextual approach is better than the conventional teaching on Organizational Behavior.